2019
DOI: 10.1155/2019/2710926
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Arsenate from Aqueous Solution onto Modified Vietnamese Bentonite

Abstract: In this study, pillared layered clays were prepared by modifying Vietnamese bentonite with polymeric Al and Fe. The obtained materials were characteristic of X-ray diffraction analysis, thermal analysis, and nitrogen adsorption/desorption isotherms. The results indicated that hydroxy-aluminum ([Al13O4(OH)24(H2O)12]7+) and poly-hydroxyl-Fe or polyoxo-Fe cations were intercalated into layers of clay, resulting in an increase of d001 values and of the specific surface areas compared with those of initial bentonit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In Table 2, the results of kf and 1/n exhibit that the sorption data is well satisfied and these values indicate the capacity and intensity of sorption, respectively. The experimental model has confirmed to be persistent with exponential dissemination of active pores, distinctive of heterogeneous surfaces [22].…”
Section: Adsorption Isothermmentioning
confidence: 73%
See 1 more Smart Citation
“…In Table 2, the results of kf and 1/n exhibit that the sorption data is well satisfied and these values indicate the capacity and intensity of sorption, respectively. The experimental model has confirmed to be persistent with exponential dissemination of active pores, distinctive of heterogeneous surfaces [22].…”
Section: Adsorption Isothermmentioning
confidence: 73%
“…The elemental iron or iron hydroxides have a high affinity for As (III) and As (V) are extensively used for the removal of arsenic [18][19][20]. Zero-valent (Fe) powders have been used or added to household filters to remove arsenic from contaminated groundwater [21][22]. There are promising material because of their large surface area, but cannot be applied in a fixed bed column, because these are fine powders and require to be converted to granular material [23].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum adsorption ( q m ) index suggested that the amendment of IIRP significantly improved the As­(V) and As­(III) adsorption capacity (Table S4). The Langmuir parameter K L can reflect the binding energy and the adsorption stability. , Accordingly, the adsorption stabilities of As­(V) and As­(III) by iron-rich particles were higher than those by the gravel substrate as indicated by the higher K L . This is in accordance with the results of sequential extractions, which showed that the adsorbed As was more stable in IIRP-TWs as compared to that in C-TWs.…”
Section: Discussionmentioning
confidence: 99%
“…The research on modification of clay minerals is applicable in various fields, and polymer modification attracts considerable attention. For example, the modified bentonite is used in water treatment to absorb organic pollutants in water, and the modified clay is used to block the migration of pollutants as well as solidify and stabilize heavy metal pollutants in EBSs [38][39][40][41]. Organic polymer modification of bentonite can increase the adsorption of organic pollutants, which has a better effect than inorganic modified materials [42].…”
Section: Discussionmentioning
confidence: 99%